Influence of Arctic light conditions on crop production and quality. Issue 4 (6th May 2021) - Mølmann, Jørgen A. B.; Dalmannsdottir, Sigridur; Hykkerud, Anne Linn; Hytönen, Timo; Samkumar, Amos; Jaakola, Laura
Abstract: The natural light conditions above the Arctic Circle are unique in terms of annual variation creating special growth conditions for crop production. These include low solar elevations, very long daily photosynthetic light periods, midnight sun/absence of dark nights, and altered spectral distribution depending on solar elevation. All these factors are known to affect the growth and the metabolism of plants, although their influence on northern crop plants has not yet been reviewed. The ongoing global warming is especially affecting the temperature × light interactions in the Arctic, and understanding the impact on crop production and plant metabolism will be important for an Arctic contribution to global food production. Arctic light conditions have a strong influence on the timing of plant development, which together with temperature limits the number of cultivars suitable for Arctic agriculture. This review compiles information from the reports about the effects of light conditions at high latitudes on growth, biomass production, flowering and quality of the crop plants and discusses the gained knowledge and the key gaps to be addressed.